Community Readiness in the Development of Community-Based Natural Tourism Village in Ngestirejo Gunungkidul - Tristanti Tristanti; Sugito Sugito; Adin Ariyanti Dewi; Yudan Hermawan (Budapest International Research and Critics University, 2022)
The development of tourism can encourage the economic growth of the community, especially in the tourism village community of Ngestirejo. In its development can not be separated from the involvement of the surrounding community, local government and private parties or companies. Various parties have supported the development of this tourist village, namely the Ngestirejo community, the Pordasi Organization (All-Indonesian Horse Sports Association) Special Region of Yogyakarta, and the local government of Gunungkidul Regency. The purpose of this study is to describe the readiness of the community in the development of community-based nature tourism villages. This research is an exploratory case study with selected informants using purposive sampling method. Data were collected through in-depth interviews, observation, and documentation. Data analysis uses the stages of data collection (data collection), data reduction (data reduction), data presentation (data display), and drawing conclusions or verification (conclutions). The result of the research is that there is a form of community readiness both in physical and non-physical terms in the development of community-based nature tourism villages.